Preventing outbreaks in burn units: the role of hygiene compliance and early warning systems - Marie Lindblad; Fredrik Huss; Eva Tano; Birgitta Lytsy; Susanne Sütterlin (Antimicrobial Resistance and Infection Control)
Abstract Background and objectives To analyse observations of staff’s hand hygiene, usage of gloves and plastic aprons, and dress code compliance at the Burn Centre, Uppsala University Hospital in Sweden, and to evaluate the association between hygiene non-compliance and outbreak periods. Furthermore, to explore the potential of using routine hygiene observations as an early warning tool for the risk of uncontrolled spread of (multidrug-resistant) bacteria. Methods Direct observations of the personnel’s compliance with hand hygiene, usage of gloves and plastic aprons, and dress code were studied in relation to two A. baumannii outbreaks in 2014 and 2020. Interrupted time series analyses were conducted from 2013 to 2017 and 2018 to 2022 to evaluate outbreak intervention measures. Rolling sums of observed hygiene errors and 90th percentiles were calculated for four-, five-, and six-month periods. Results During the study, 13,216 direct observations showed hygiene compliance ranging from 70 to 100% per category. Infection control interventions significantly reduced non-compliance after both outbreaks, with sustained improvements for two years following the first outbreak. Rolling four- to six-month sums, using 90th percentile thresholds of seven, nine, and eleven non-compliances predicted A. baumannii outbreaks. Conclusion In this setting, compliance levels above 97% were consistently observed during outbreak-free periods, suggesting a potential protective effect. Focus on non-compliance as a key metric and rolling sums of non-compliance, may support early detection of increased outbreak risk and guide preventive interventions.